An Economic Analysis of Lac Marketing in Kanker District of Chhattisgarh - Pal, Govind; Patel, Bharati (Indian Forester, 2013)
Lac is recognized as a high value cash crop and management of its marketing plays a vital role for better returns. The present paper examines the marketing costs and price spread in marketing of lac in the state of Chhattisgarh. District Kanker has been selected purposively for the present study. Data on marketing costs, margins and constraints in lac marketing is collected from lac growers, market functionaries and manufacturers. The lac grower received ` 75 per kg. which amounts to 86.15 per cent share in consumers’ price. The primary purchaser’s margin was ` 260 per quintal (2.99 per cent of consumers’ price) and incurred ` 63 per quintal on marketing cost (0.72 per cent of consumers’ price). The total marketing cost paid by the wholesaler was ` 743 per quintal (8.53 per cent of consumers’ price). The wholesaler’s marketing margin was ` 140 per quintal (1.61 per cent of consumers’ price). ’Arhat’ charges were 3 per cent of the transacted amount. There was tremendous scope to increase the profitability of lac growers in the study area by adopting proper marketing and processing techniques.